2005
DOI: 10.1007/s00424-005-1400-z
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin release during endotoxaemic shock in mice lacking inducible nitric oxide synthase

Abstract: We tested the hypothesis that nitric oxide (NO) arising from the action of inducible nitric oxide synthase (iNOS) is responsible for the deficiency in vasopressin (AVP) release and consequent hypotension during endotoxaemic shock. Wild-type (WT) and iNOS knockout mice (iNOS(-/-)) were given either saline or Escherichia coli lipopolysaccharide (LPS, 1.0 mg/kg i.v., final volume 0.03 ml). Mean arterial blood pressure (MAP) was measured and plasma AVP levels determined before and after LPS or saline injection. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
9

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 30 publications
2
11
0
9
Order By: Relevance
“…A recent study of our laboratory, using genetic mice lacking iNOS, showed that WT animals have a transitory increase in AVP plasma level after 2 h of LPS injection, after which its values return near basal levels. While those iNOS KO mice had higher AVP concentrations during the fourth and sixth hours when compared with WT group, which could be reflected in beneficial attenuation of hypotension (Carnio et al, 2005). Together, these data confirmed an inhibitory action of NO in AVP release.…”
Section: Discussionsupporting
confidence: 65%
“…A recent study of our laboratory, using genetic mice lacking iNOS, showed that WT animals have a transitory increase in AVP plasma level after 2 h of LPS injection, after which its values return near basal levels. While those iNOS KO mice had higher AVP concentrations during the fourth and sixth hours when compared with WT group, which could be reflected in beneficial attenuation of hypotension (Carnio et al, 2005). Together, these data confirmed an inhibitory action of NO in AVP release.…”
Section: Discussionsupporting
confidence: 65%
“…There were no differences between the two groups in baseline rates of apoptosis or degree of macrophage infiltration in either organ. In both the lung and the liver, LPS induced a statistically significant increase in apoptosis in both groups ( In mice, LPS-induced hemodynamic responses are regulated, in part, via the NO system (15,16). To determine if endogenous GR regulates the levels of vascular NOS, control and GR EC KO mice (n = 3 per group) were treated with vehicle or LPS (12.5 mg/kg) and aortic gene expression via qPCR was examined at 8 h post-LPS treatment.…”
Section: Loss Of Endothelial Gr Does Not Affect Apoptosis or Macrophagementioning
confidence: 99%
“…Elevated levels of NO may contribute to autonomic dysfunction (52) and have direct inhibitory effects on vasopressin secretion (5). Sustained elevation of hormone levels following endotoxin challenge in mice was seen in iNOS knockouts or after pharmacologic NO inhibition (53)(54)(55).…”
Section: Vasopressin In Septic Shockmentioning
confidence: 99%